ACM Committee Proposes RTA System Guidelines. (Communications of the ACM, 2021)
The article briefly discusses the organization the Association for Computing Machinery's U.S. Technology Policy Committee (ACM USTPC) proposals for guidelines concerning the oversight, use, and design of Remote Testing Administration (RTA) software.